1993
DOI: 10.1038/clpt.1993.66
|View full text |Cite
|
Sign up to set email alerts
|

Altered patterns of drug metabolism in patients with acquired immunodeficiency syndrome

Abstract: Caffeine was used to assess acetylation status and indexes of oxidative drug metabolism (demethylation, xanthine oxidation, and 8-hydroxylation) in a control group and in three groups of patients infected with human immunodeficiency virus (HIV): patients with acquired immunodeficiency syndrome (AIDS) who had acute illnesses, stable patients with AIDS, and asymptomatic patients infected with HIV. The prevalence of apparent slow acetylation was greater in AIDS patients with acute illnesses compared with control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(57 citation statements)
references
References 0 publications
1
54
1
1
Order By: Relevance
“…For patients who were phenotyped more than once, changes in acetylation phenotype from fast to slow were associated with progression of HIV infection. Interestingly, an earlier report had noted that the prevalence of apparent slow acetylation phenotype was greater in AIDS patients with acute illnesses (27 out of 29, 93%) compared with control subjects (18 out of 29, 62%) (Lee et al, 1993). A subsequent study compared 30 AIDS patients (with and without an acute illness) with 30 healthy control subjects for their NAT2 acetylation phenotype and genotype and reported numerous discrepancies between phenotype and genotype (O'Neil et al, 2000a).…”
Section: Downloaded Frommentioning
confidence: 99%
“…For patients who were phenotyped more than once, changes in acetylation phenotype from fast to slow were associated with progression of HIV infection. Interestingly, an earlier report had noted that the prevalence of apparent slow acetylation phenotype was greater in AIDS patients with acute illnesses (27 out of 29, 93%) compared with control subjects (18 out of 29, 62%) (Lee et al, 1993). A subsequent study compared 30 AIDS patients (with and without an acute illness) with 30 healthy control subjects for their NAT2 acetylation phenotype and genotype and reported numerous discrepancies between phenotype and genotype (O'Neil et al, 2000a).…”
Section: Downloaded Frommentioning
confidence: 99%
“…[243] Moreover, Lee et al demonstrated that AIDS patients with acute illnesses had altered patterns of drug metabolism. [244] Data collected from studies performed in healthy volunteers should thus be extrapolated carefully to HIVinfected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Although trimethoprim-sulphamethoxazole is effective in the treatment of pneumonia caused by Pneumocystis carinii in AIDS patients, its use is often limited by severe side effects occuring in about 50% of treated patients [3]. It has been reported that the prevalence of apparently slow acetylators was higher in acutely ill AIDS patients than in stable patients or control subjects [4]. More recently, it has also been observed that the prevalence of the slow acetylator phenotype was greater in AIDS patients with sulphonamide hypersensitivity than in sulphonamide-tolerant patients, leading to the suggestion that acetylator phenotype is a risk factor for the observed toxicity [5].…”
mentioning
confidence: 99%